Triathlon for the every woman you can be a triathlete. Yes. You. - Atwood, Meredith (New York Da Capo Lifelong, 2019)
"Meredith Atwood was a tired, overworked wife and mom who never thought she'd run a mile, let alone swim, bike, and run. But after trial, error, tears, chafing, and a lot of grit, she went from stressed-out lawyer to an IRONMAN 70.3 triathlete in just over a year. Now a triathlon coach and four-time IRONMAN triathlete, Meredith shares her hard-won widsom and tips, anecdote, and laughs. In Triathlon for the Every Woman you'll find: a basic blueprint for getting started that will inspire you to find your motivation. Lists of equipment necessary to do your first (or next!) triathlon-what you don't need, what you do, and how not to go broke getting it. Expert nutrition advice that won't starve, shame, or sabotage you. Compact and easy-to-implement training plans that won't kill you. Practical advice on how to fit triathlon into your busy life." -- Page 4 of cover.
Making the decision to become a triathlete -- Getting started -- Coaching and community -- Safety and smartness -- A brief interlude on data -- The swim -- The bike -- The run -- Other important training stuff -- The mental game -- Nutrition and the scale -- The trifecta: family, work, and triathlon -- Tri through tough times -- Lost in transition -- Race preparation and race day -- To long-distance triathlon and beyond.
Includes index.
Keywords: Cycling -- Training; Running -- Training; Swimming -- Training; Triathlon -- Training